Measuring The Differences Of Work-Life Balance And Employee Engagement In Y-Generation Employees In Cikande Modern Serang Banten Area And Regional Area Of Cikupa Mas Tangerang Banten - Nafiudin Nafiudin (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to find out how the difference between Work-life Balance, Employee Engagement Generation Y in Cikupa Mas Region Tangerang Banten and Cikande Modern Serang Banten and test whether the variable work- life balance affect employee engagement, his type of research is quantitative by using comparison design, while the research data obtained through the spread of questionnaires and samples used are 70 employees from each region of the sampling technique used is the accidental sampling. based on the results of analysis using independent test t-test that work-life balance between Y-employed employees who work in the area of Cikupa and Cikande perceived differently, but that occurs in Employee Engagement variables between employees working in the area of Cikupa and Cikande did not experience differences.